Axe 66. - Galerie Contrastes, Bruxelles (Bruxelles : Galerie Contrastes, 1968)
Lapière, André ; Londot, Louis-Marie ; Pirrad, Michel ; Souply, Emile ; Van Espen, Jean M. ; Warrand, Michel
Axe 66, Galerie Contrastes, Bruxelles, du 14 février au 4 mars 1968
boek